Multicenter Evaluation of a Kit for Activated Protein C Resistance on Various Coagulation Instruments Using Plasmas from Healthy Individuals - Rosén, S; Johansson, K; Lindberg, K; Dahlbäck, B; (for the APC resistance study group) (Thrombosis and Haemostasis, 1994)
Recently a new hemostatic disorder has been described which appears to be an important risk factor for familial thromboembolism. The disorder is characterized by a poor anticoagulant response to activated Protein C (APC) and has been shown to be due to lack of an APC cofactor activity which is a property of factor V.A kit for determining the response of plasma samples towards addition of APC in an APTT-based assay - COATEST APC Resistance -has been evaluated on 35 coagulation instruments in a multicenter study involving 32 laboratories. A lyophilized normal plasma and identical plasma aliquots from 20 individuals, one of whom had a borderline resistance to APC, were analysed in each laboratory and the sensitivity of each plasma to APC was determined as the ratio between the clotting times obtained in the presence and absence of APC (APC ratio).The plasma from the individual with a borderline resistance to APC activity was correctly classified as the lowest responder in each laboratory, with an APC ratio in the range 1.6-2.4. In comparison, plasmas from individuals with a pronounced response to APC activity resulted in APC ratios above 3.4 in most cases. Interestingly, although the actual APT time for a plasma from a given individual showed a more than 10 s difference due to the type of instrumentation used, the variation in the APC ratio was limited. A similar discrimination was also obtained from evaluation of the actual prolongation of the clotting time in the presence of APC.The intra-laboratory coefficient of variation for the clotting times were on average 2.0% and 3.9% in the absence and presence of APC, respectively, indicating that the precision for the prolonged clotting times obtained in the presence of APC is sufficient to allow a safe assignment of the APC response. The APC ratio for the lyophilized normal plasma was 2.7 ± 0.2 (2 S.D.) illustrating a narrow distribution between instruments which shows the feasibility of including such plasma for assay validation. Altogether, the results indicate that all the coagulation instruments included in the study can be used for detection of individuals with resistance to APC activity through determination of the APC ratio or the prolongation time.